Risk assessment and management of genetically modified organisms under Australia's Gene Technology Act - Linacre, Nicholas A.; Falck-Zepeda, José B.; Komen, John; MacLaren, Donald (International Food Policy Research Institute, 2006)
Compared to both Canada and the United States, Australia has been slow to approve commercial planting of transgenic crops. Two probable reasons exist for the slow approval rate of transgenic crops in Australia. The first reason is community perceptions about the risks associated with transgenic technologies. The second is the regulatory framework currently employed to approve commercial releases. This paper examines some of the potential regulatory issues that may be affecting the review process and approval of transgenic technologies. First we provide a brief introduction to the regulatory structure in Australia, second we consider the impact of regional, national and state jurisdictions, third we argue that the regulator needs to consider the use of benefits analysis in decision making, fourth we argue for the use of probabilistic risk assessments in certain circumstances, and fifth we look at potential problems inherent in majority voting in a committee and recommend alternatives.--Authors' Abstract